Homo supermercatus poważnym wyzwaniem moralnym dla kaznodziejstwa - Drożdż, Alojzy (Studia Pastoralne, 2026)
Human is „moral being” regardless of conditions and the times in which he lives. It results from the fact, that human is a person, it means that he is spiritual-corporeal being, someone who is rational and independent. Despite the fact that the man is exposed to McDonaldization, subjected to numerous crises, it should be noted that he is still religious being and occurred processes did not deprive him of religious sense. Human is still sensitive to religious questions, even though he looks very often for answer outside Christianity, which is old – fashioned in media. It is essential challenge not only for preaching but also for whole Christian formation. A long time ago, Maurice Blondel said, that: „the times are the same like people are”. As it is known people are either moral good or moral bad. Tertium non datur. This also applies to human morality, which today is sometimes labeled as homo supermercatus. An important challenge is consumerist life style of many people, who live most of the time without awareness of development of appropriate hierarchy of values and necessary spiritual needs. These people usually satisfy their material needs without thinking of human dignity and their Christian vocation. Homo consumens – is a person, who is suspended between gift and commodity. Detailed sociological and psychological analysis give us a lot of arguments about the behavior of present – day human. This man seems to have many features, which indicate that, „he desires to have more”, instead of „to be a human more and more”. Today, principle is known: I consume, therefore I am. Strong influence of ethical utilitarianism on daily culture of life was noticed long ago. For example – in the book The New Economic Gospel of Consumption, written by E. Cowdrick in 1927, we can find interesting opinion, that we live in times, when people are forced to regular consume of goods and services. It also impinges on assessment of current homiletic thinking. Author emphasizes, using criteria from ethic of J. Woroniecki, that the human always was and is just jealous, mistrustful, suspicious and first and foremost selfish and very greedy. It causes, that he is a person of many crises, which can be solved effectively by homiletic teaching. Analyzing behavior, attitudes and basic sources of numerous crisis (identity crisis, family crisis, political crisis, educational crisis etc.) of consumerist human, author develop thought of Marciano Vidal, that this person is a man of „lost ethical home”. Under the pulpit and before the alter – we do not have today – saying colloquially – „empty people” and „neuter people”. We have deeply hurt people in their humanity. Moreover we have people with many difficulties in faith. There are difficulties arising from human life experience and civilization’s difficulties. It turns out that only Christianity, with its integrity of salvation, is able to help such people effectively.